(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The primary goal of this system is to have a dependable and smooth project and product monitoring and evaluation process in e-commerce logistics. 1. In order for users to know the project progress, monitor, and order incoming and outgoing products, the system must manage project management, asset management, warehousing, and procurement. This system is designed to provide status information and identify work on the company’s behalf. The main goal is to develop a system that will assist Logistics 1 employees in completing their work more quickly by utilizing an automated system rather than a manual procedure. The development team established project management, asset management, warehousing, and procurement departments. This system will assist the logistics staff in monitoring and evaluating every project and product that comes into the company. A programmer created a system that will assist both staff in managing work monitoring and evaluation. The system will greatly benefit e-commerce and logistics by reducing their workload and the manual labor of logistics personnel. The developed system is a huge help to the logistics staff. We need to collaborate with every company and worker, especially now that we’re facing an economic standard, so the development team creates a system that will help the eCommerce and logistics staff monitor and evaluate all the projects and products from every department.